2018
DOI: 10.1038/s41598-018-35859-6
|View full text |Cite
|
Sign up to set email alerts
|

Engineered K1F bacteriophages kill intracellular Escherichia coli K1 in human epithelial cells

Abstract: Bacterial infections can be treated with bacteriophages that show great specificity towards their bacterial host and can be genetically modified for different applications. However, whether and how bacteriophages can kill intracellular bacteria in human cells remains elusive. Here, using CRISPR/Cas selection, we have engineered a fluorescent bacteriophage specific for E. coli K1, a nosocomial pathogen responsible for urinary tract infections, neonatal meningitis and sepsis. By confocal and live microscopy, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 69 publications
4
65
0
Order By: Relevance
“…n = 3 in each case. (2020) 10:8903 | https://doi.org/10.1038/s41598-020-65867-4 www.nature.com/scientificreports www.nature.com/scientificreports/ Confocal microscopy image analysis also confirmed observations of previous studies performed in T24 human urinary epithelial cells 19 , showing the ability of phage K1F-GFP to locate and infect E. coli EV36-RFP in a human cell environment and the formation of intracellular vacuoles containing phage-aggregates in human cells.…”
Section: Internalisation and Degradation Of Bacteria And Phages In Husupporting
confidence: 84%
See 3 more Smart Citations
“…n = 3 in each case. (2020) 10:8903 | https://doi.org/10.1038/s41598-020-65867-4 www.nature.com/scientificreports www.nature.com/scientificreports/ Confocal microscopy image analysis also confirmed observations of previous studies performed in T24 human urinary epithelial cells 19 , showing the ability of phage K1F-GFP to locate and infect E. coli EV36-RFP in a human cell environment and the formation of intracellular vacuoles containing phage-aggregates in human cells.…”
Section: Internalisation and Degradation Of Bacteria And Phages In Husupporting
confidence: 84%
“…It is notable that both stains are membrane-impermeable and thus the fluorescent signal is only present in the brief interval from initial lysing to complete dismantlement of the bacterial membrane. The ability and efficiency of phage K1F-GFP to locate and infect intracellular E. coli EV36 in a human cell environment has been confirmed in previous studies 19 , however, the signal stability of GFP is often a point for discussion. We therefore initially assessed the fluorescent signal emitted by phage K1F-GFP during infection in E. coli EV36 using flow cytometry.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The adsorption of the phage on the surface of bacteria is the first and most important step in the process of phage infection [31]. In this study, the genes gp52 (Figure 8) indicated that the tail fiber proteins gp52 and gp53 had the ability to recognize and capture A. baumannii.…”
Section: Identification the Function Of The Phage Tail Fiber Protein mentioning
confidence: 60%